Impacts of Co-Management Activities on Forests and Households in Guinea - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
Guinea has 147 forest reserves, encompassing more than 1.2 million hectares, managed by Guinea’s Direction Nationale des Eaux et Forêts (DNEF) (http://www.eaux-forets.gouv.gn/). Most of these reserves have experienced severe resource degradation and human encroachment. From 2005 to 2008, the Landscape Management of Improved Livelihoods (LAMIL) project operated in four of Guinea’s forest reserves. The project— managed by DNEF, the Center for International Forestry Research (CIFOR) (https://www.cifor.org/), the World Agroforestry Centre (ICRAF) (http://www.worldagroforestry.org/), and the U.S. Forest Service (USFS) (https://www.fs.fed.us/)—was designed to improve forest governance and raise the incomes of farmers and foresters. A recent study by researchers from Virginia Tech and CIFOR assessed the impacts of this forest co-management project on forest cover and indicators of household well-being.